2021
DOI: 10.1007/s11606-021-07136-2
|View full text |Cite
|
Sign up to set email alerts
|

Are Veterans Getting Their Preferred Depression Treatment? A National Observational Study in the Veterans Health Administration

Abstract: Background Physician responsiveness to patient preferences for depression treatment may improve treatment adherence and clinical outcomes. Objective To examine associations of patient treatment preferences with types of depression treatment received and treatment adherence among Veterans initiating depression treatment. Design Patient self-report surveys at treatment initiation linked to medical records. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…We cannot determine how clinicians and patients selected their care plan. A recent study found patients were more likely to follow up with depression care plans when they match their preferences (Leung et al, 2022). Clinicians, especially physicians, may benefit from additional training about how to engage in patient-centered discussions incorporating the assessment of contextual factors contributing to patients' symptoms, determination of treatment preferences, and care planning and follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot determine how clinicians and patients selected their care plan. A recent study found patients were more likely to follow up with depression care plans when they match their preferences (Leung et al, 2022). Clinicians, especially physicians, may benefit from additional training about how to engage in patient-centered discussions incorporating the assessment of contextual factors contributing to patients' symptoms, determination of treatment preferences, and care planning and follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients who receive their preferred treatment are more likely to be adherent to it. 22 Some postulate that the factors linked to adherence may be divided into different categories (modifiable, partially modifiable, and non-modifiable). 23 Following this model, factors such as patient attitudes and beliefs including preferences for treatment and beliefs about the etiology of depression should be addressed in the interventions to increase adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The primary first-line treatments for depression are psychotherapy, anti-depressant medication, and their combination (Qaseem, Barry, & Kansagara, 2016). Most patients initiating depression treatment prefer psychotherapy (Gelhorn, Sexton, & Classi, 2011; Leung et al, 2021; van Schaik et al, 2004), but psychotherapy is substantially more expensive and time-consuming than ADM (Koeser, Donisi, Goldberg, & McCrone, 2015; Ross, Vijan, Miller, Valenstein, & Zivin, 2019) and is also less accessible than ADM due to the fact that primary care physicians can prescribe ADMs but psychotherapy requires access to a mental health specialist.…”
Section: Introductionmentioning
confidence: 99%